Nicotinamide Riboside Improves Stemness of Human Adipose-Derived Stem Cells and Inhibits Terminal Adipocyte Differentiation - Somaiah Chinnapaka; Hamid Malekzadeh; Zayaan Tirmizi; José A. Arellano; Asim Ejaz (MDPI AG, 2023)
Adipose tissue plays a crucial role in maintaining metabolic homeostasis by serving as a storage site for excess fat and protecting other organs from the detrimental effects of lipotoxicity. However, the aging process is accompanied by a redistribution of fat, characterized by a decrease in insulin-sensitive subcutaneous adipose depot and an increase in insulin-resistant visceral adipose depot. This age-related alteration in adipose tissue distribution has implications for metabolic health. Adipose-derived stem cells (ASCs) play a vital role in the regeneration of adipose tissue. However, aging negatively impacts the stemness and regenerative potential of ASCs. The accumulation of oxidative stress and mitochondrial dysfunction-associated cellular damage contributes to the decline in stemness observed in aged ASCs. Nicotinamide adenine dinucleotide (NAD+) is a crucial metabolite that is involved in maintaining cellular homeostasis and stemness. The dysregulation of NAD+ levels with age has been associated with metabolic disorders and the loss of stemness. In this study, we aimed to investigate the effects of nicotinamide riboside (NR), a precursor of NAD+, on the stemness of human ASCs in cell culture. Our findings reveal that adipogenesis is accompanied by an increase in mitochondrial activity and the production of reactive oxygen species (ROS). However, treatment with NR leads to a reduction in mitochondrial activity and ROS production in ASCs. Furthermore, NR administration improves the stemness-related genes expression in ASCs and mitigates their propensity for adipocyte differentiation. These results suggest that NR treatment holds promise as a potential strategy to rejuvenate the stemness of aged ASCs. Further investigations, including in vivo evaluations using animal models and human studies, will be necessary to validate these findings and establish the clinical potential of this well-established drug for enhancing the stemness of aged stem cells.